(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article analyzes the state of study of dendrophagous lepidopthers in foreign countries and Uzbekistan. According to the analysis, most of the research carried out in foreign countries are aimed at studying the impact of urbanization intensity in cities on the diversity of butterflies. It has been argued that the urbanization process is one of the most important threats to biodiversity. No specific studies have been conducted in Uzbekistan on dendrophagous lepidopthers cells.